PENGARUH METODE INKUIRI TERHADAP HASIL BELAJAR MATA PELAJARAN AKIDAH AKHLAK - Anis Fauzi; Fernanda Anggi Wulandari (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
The inquiry method, characterized by systematic reasoning and guided exploration, is crucial in enhancing student engagement and learning outcomes. This research was conducted in response to concerns regarding the perceived lack of interest and lower achievement in the Akidah Akhlak subject among seventh-grade students at MTs Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi during the 2020/2021 academic year. The purpose of this study was to examine the impact of the inquiry method on student learning outcomes. A correlational quantitative approach was employed, with the entire seventh-grade class (60 students) selected through census sampling. Data were collected using observation assessment rubrics and daily test scores, and analyzed using the Product Moment formula and linear regression with the assistance of SPSS 16.0 for Windows. The findings revealed a significant positive correlation between the use of the inquiry method and student learning outcomes, with an r-value of 0.530 and a significance level of 0.000. The coefficient of determination (R²) was calculated at 0.281, indicating that the inquiry method accounts for 28.1% of the variance in student learning outcomes. These results suggest that the inquiry method is effective in improving student performance in the Akidah Akhlak subject. Therefore, it is concluded that the application of the inquiry method positively influences the learning outcomes of seventh-grade students at MTs Roudlotul Muta'allimin Simbar Tampo Cluring Banyuwangi in the 2020/2021 academic year.